Rational Mix Design of Lightweight Concrete for Optimum Strength - Th. Dawood, Eethar; Ramli, Mahyuddin (2008)
In this study, structural lightweight concretes produced by Coarse lightweight Crushed brick and Fine light weight crushed brick (CLWA & FLWA) were investigated.